Progress in Bi2WO6-Based Materials for Electrochemical Sensing and Supercapacitor Applications - Khursheed Ahmad; Dhanabalan Karmegam; Tae Hwan Oh (Molecules)
Recently, the design and fabrication of novel electrode materials for electrochemical and electronic devices have received the widespread attention of the scientific community. In particular, electrochemical sensors and supercapacitors (SCs) involve the use of catalysts, which can enhance the electrochemical reactions at the surface of the electrode. Bismuth tungstate (Bi2WO6) is a cost-effective and efficient electrode material with decent optoelectronic properties and stability. The properties of Bi2WO6 can be improved by incorporating carbon-based materials, and the resulting composite may be a promising electrode material for electrochemical sensing and SCs. As per the available reports, Bi2WO6 has been combined with various nanostructured and conductive materials for electrochemical sensing and SC applications. This review discusses synthetic methods for the preparation of Bi2WO6. Progress in the construction of hybrid composites for electrochemical sensing and SC applications is reviewed. The Conclusion section discusses the role of electrode materials and their limitations with future perspectives for electrochemical sensing and SCs. It is believed that the present review may be useful for researchers working on Bi2WO6-based materials for electrochemical sensing and SC applications.